Effectiveness of scapular clock exercises in scapular dyskinesia in post operative cardiac patients: A randomized clinical trial - Izza Ayub; Sana Zahir; Aqsa Shahid; Rohail Amir Babar; Amir Mushtaq (The Rehabilitation Journal)
Background: Scapular dyskinesia is a frequent complication after cardiac surgery due to thoracic immobility, pectoral tightness, and muscle imbalances, contributing to persistent shoulder pain and functional deficits.